Determination of potassium ions in biodiesel using a nickel(II) hexacyanoferrate-modified electrode - Castilho, Michelle de Souza [UNESP]; Stradiotto, Nelson Ramos [UNESP] (Elsevier B.V., 2008)
in this work. nickel hexacyanoferrate-modified electrode was developed to determine potassium ions in biodiesel by potentiometry. The modified electrodes exhibit a linear response to potassium ions in the concentration range of 4.0 x 10(-5) to 1.0 x 10(-2) mol L-1, with a detection limit of 1.9 x 10(-5) mol L-1. and a near-Nernstian slope (53-55 mV per decade) at 25 degrees C. The method developed in this work was compared with flame photometry and the potassium concentration found in biodiesel showed that the modified electrode method gives results similar to those obtained by flame photometry. (C) 2007 Elsevier B.V. All rights reserved.
Keywords: biodiesel; modified electrodes; nickel(II) hexacyanoferrate; potassium ions